2017
DOI: 10.11113/jt.v79.10410
|View full text |Cite
|
Sign up to set email alerts
|

Double Bootstrap Control Chart for Monitoring Sukuk Volatility at Bursa Malaysia

Abstract: The bootstrap approach on control limit has provided a solution in solving uncertainty estimation problem in control chart performance. However, the limitation of this standard chart has shown to be less efficient and invalidation at certain magnitude shift, especially the monitored sample data is assumed from skewed family distribution. Thus, in this study, a double bootstrap base-model and its control limit is developed in order to improve the efficiency and decrease the invalidation chart performance. In or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…This process continues until a new bootstrap dataset is formed with N samples. It was reported in [49] that bootstrapping is highly effective when applied to a small sample size (N < 30). In the case of a larger sample size, bootstrapping offers the benefits of improved accuracy in statistical estimation and increased percentage of estimation effectiveness and is independent of the sample distribution.…”
Section: Bootstrap Methodsmentioning
confidence: 99%
“…This process continues until a new bootstrap dataset is formed with N samples. It was reported in [49] that bootstrapping is highly effective when applied to a small sample size (N < 30). In the case of a larger sample size, bootstrapping offers the benefits of improved accuracy in statistical estimation and increased percentage of estimation effectiveness and is independent of the sample distribution.…”
Section: Bootstrap Methodsmentioning
confidence: 99%
“…Bootstrap is a reliable method given the lack of researchers adding this method in daily cases of COVID-19 forecasting. Many studies have shown that the bootstrap resampling technique provides a more accurate estimation [17,[40][41][42].…”
Section: Limitations and Future Recommendationmentioning
confidence: 99%